Enhanced dye-removal performance of Cu-TiO2-fly ash composite by optimized adsorption and photocatalytic activity under visible light irradiation - Devagi, Kanakaraju; Muhamad Akif Aizuddin, Jasni; Andrea, Pace; Muhamad Hazim, Ya (Springer Nature, 2021)
The performance of Cu/TiO2/FA composite, a hybrid adsorbent-photocatalyst consisting of copper-doped titania particles supported on fly ash, was optimized, under visible light irradiation, for the removal of the model dye pollutant methyl orange (MO) by using a response surface methodology and Box-Behnken experimental design. Three independent variables were considered for the optimization study: catalyst/solvent dosage (0.5 – 2.0 g/L), irradiation time (30–120 min), and the initial concentration (5– 25 ppm) of the dye. A 99.91% rate of removal was achieved using 2 g/L dosage, 5 ppm initial concentration, and 100 min of irradiation time as the optimal operating conditions. The recorded trends support the hypothesis of a combined and synergic adsorption-photocatalytic degradation process which fully exploits the “capture and destroy” approach for pollutant removal.